Pain Perception Model in people with Migraine Headache: The Interplay of Intolerance of Ambiguity and Fear of Disease Progression - Roshanghias , Zahra; Jabalameli, Sheida; Janatian , Sima; Sajjadian, Parinaz Sadat (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: Migraine headaches are often associated with complex psychological factors that can influence pain perception. This study aims to explore the pain perception model in individuals with migraine headaches, focusing on the role of intolerance of ambiguity and the mediating effect of fear of disease progression.Methods and Materials: A descriptive-correlational design was employed, involving 207 adult participants (aged 30 to 60) diagnosed with migraines in Tehran, 2025. Participants completed validated   McGill Pain Questionnaire (MPQ), Ahwaz Migraine Headache Questionnaire (AMQ), Ambiguity Tolerance Scale (ATS), and Short Form of the Fear of Progression Questionnaire (FOP-Q-SF). Statistical analyses were conducted to examine the relationships among these variables. SPSS version 27 software was used to perform descriptive statistics and Spearman correlation, and SmartPLS version 4 software was used to analyze the path between variables.Results: The results indicated that the variable Tolerance of Ambiguity had a significant negative direct effect on Fear of Disease Progression (β = -0.417, p < 0.001). At the same time, the variable Tolerance of Ambiguity also had a significant negative direct effect on Pain Perception (β = -0.331, p < 0.001), leading to a reduction in pain perception. Based on the results, Tolerance of Ambiguity had a significant negative indirect effect on Pain Perception through Fear of Disease Progression (β = -0.210, p < 0.001).Conclusion: These results underscore the intricate relationships between psychological distress, resilience, and pain perception in individuals with migraine headaches. Enhancing resilience may serve as a potential intervention to mitigate the adverse effects of psychological distress on pain experiences.